If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = k * k + -12k + 35 Multiply k * k 0 = k2 + -12k + 35 Reorder the terms: 0 = 35 + -12k + k2 Solving 0 = 35 + -12k + k2 Solving for variable 'k'. Combine like terms: 0 + -35 = -35 -35 + 12k + -1k2 = 35 + -12k + k2 + -35 + 12k + -1k2 Reorder the terms: -35 + 12k + -1k2 = 35 + -35 + -12k + 12k + k2 + -1k2 Combine like terms: 35 + -35 = 0 -35 + 12k + -1k2 = 0 + -12k + 12k + k2 + -1k2 -35 + 12k + -1k2 = -12k + 12k + k2 + -1k2 Combine like terms: -12k + 12k = 0 -35 + 12k + -1k2 = 0 + k2 + -1k2 -35 + 12k + -1k2 = k2 + -1k2 Combine like terms: k2 + -1k2 = 0 -35 + 12k + -1k2 = 0 Factor a trinomial. (-7 + k)(5 + -1k) = 0Subproblem 1
Set the factor '(-7 + k)' equal to zero and attempt to solve: Simplifying -7 + k = 0 Solving -7 + k = 0 Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + k = 0 + 7 Combine like terms: -7 + 7 = 0 0 + k = 0 + 7 k = 0 + 7 Combine like terms: 0 + 7 = 7 k = 7 Simplifying k = 7Subproblem 2
Set the factor '(5 + -1k)' equal to zero and attempt to solve: Simplifying 5 + -1k = 0 Solving 5 + -1k = 0 Move all terms containing k to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1k = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1k = 0 + -5 -1k = 0 + -5 Combine like terms: 0 + -5 = -5 -1k = -5 Divide each side by '-1'. k = 5 Simplifying k = 5Solution
k = {7, 5}
| 2(x-5)+2-3(5-2x)=16 | | k/4+3=6 | | 13z/9+9=3z-33 | | 3/5*3 | | 5(x+7)=25(x+1) | | s(s+0.89)=92.99 | | -4x-4=3x-25 | | x+3x-670=2658 | | p*p-p-6=0 | | 4sin^2x=1+4cosx | | 4p-49=9p/5+6 | | 4.5+.2p=6.1 | | 620-4x+x=3720 | | x+17=27-9x | | 16b/9+8=3b-36 | | 3(2a)-1/4(2a)+2 | | 4.5+.2=6.1 | | 3/4x=8 | | 11d/8=4d-147 | | x+4x-620=3720 | | 9=x+1-3x | | X-3=6x+42 | | -3(5-9v)=25+7 | | -12=f/0.2 | | 12=1-5n-6n | | x-3x+620=2928 | | -3m+10=25 | | X+7=-3x+51 | | -16=4+5r+5r | | 3(1.5)-1/4(1.5)+2 | | x-3x+530=2994 | | 15y^2+7y-2=0 |